2002
DOI: 10.1080/014850102317267481
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Lectin Receptors on the Membrane Surface of Sperm of Fertile and Subfertile Boars by Flow Cytometry

Abstract: Studies suggest that carbohydrates are important in different stages of fertilization. Plasma membrane changes accompanying in vitro capacitation and acrosome reaction (AR), such as removal or appearance of specific glycoproteins, have been studied using lectins that bind specifically to carbohydrate residues. In specialized artificial insemination farms and semen production centers, identification of boars with decreased fertilization ability (subfertility) is a newborn necessity. This investigation is a sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 29 publications
(13 reference statements)
1
21
0
3
Order By: Relevance
“…AS-A is present in the boar capacitated sperm and exposes mannose, N-acetylglucosamine and=or sialic acid. These results agree with previous reports describing the presence of these glycosidic residues in boar sperm capacitated membrane [13,14]. Indirect immunofluorescence and electron microscopy studies showed that AS-A is located on the membrane of the sperm head and on the post-acrosomal region, and can also be detected in the acrosome of several mammalian species [20,27].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…AS-A is present in the boar capacitated sperm and exposes mannose, N-acetylglucosamine and=or sialic acid. These results agree with previous reports describing the presence of these glycosidic residues in boar sperm capacitated membrane [13,14]. Indirect immunofluorescence and electron microscopy studies showed that AS-A is located on the membrane of the sperm head and on the post-acrosomal region, and can also be detected in the acrosome of several mammalian species [20,27].…”
Section: Discussionsupporting
confidence: 94%
“…The distribution of these molecules changes during capacitation and acrosome reaction [13,14]. The participation of mannose in binding of sperm to human ZP is established [3,18].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, glycocalyx modifications occurring during mammalian spermatozoa maturation in the epididymis are believed to confer fertilizing ability to the spermatozoon (Eddy, 1988). Moreover, the characteristics of changes occurring in the glycocalyx of boar spermatozoa during capacitation and acrosome reaction have implications for fertility (Jiménez et al, 2002). Based on the available literature, it seems reasonable to suggest that the modifications of the turkey sperm glycocalyx observed in our study could have functional repercussions that affect the fertility of in vitro stored semen.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27][28] One hundred cells were observed to evaluate semen samples. 28 Only ejaculates showing more than 85% progressive motility, at least 90% viability, and less than 10% abnormality were used. 29 Capacitation Semen samples were washed twice to remove the seminal plasma by adding 1 mL of phosphate-buffered saline (PBS) to an equal volume of semen followed by centrifugation at 600 g for 5 minutes.…”
Section: Semen Samplesmentioning
confidence: 99%